Gempa Nusantara: a database of 7380 macroseismic observations for 1200 historical earthquakes in Indonesia from 1546 to 1950 - Martin, Stacey S. (2023)
We present a new database called Gempa Nusantara, which is a collection of 7380 macro-seismic observations for 1200 historical earthquakes in Indonesia between 1546 and 1950 C.E. using the European Macroseismic Scale (1998). Scrutinizing preserved original, first-hand, private, and official documentation from the colonial period in Indonesia, we could examine the completeness of this written record based on the gradual expansion of European influence in the Indonesian Archipelago. As the largest database of uniformly assessed macroseismic intensities ever assembled for Indonesia, our database can correct errors and fill gaps in other contemporary studies of historical Indonesian earthquakes, as well as paleoseismic studies such as the coral paleogeodetic record from Sumatra. Remarkably, given the presence of several major active faults, conclusive evidence of coseismic surface ruptures during the colonial period was limited to just two events in 1909 and 1933. Our reliance on original materials also allowed us to document extreme coseismic ground failure in Sumatra in 1936 with striking similarities to those observed on Sulawesi in 2018. From the perspective of seismic hazard in a rapidly urbanizing nation, we show that the frequencies of observed intensities over the duration of our database cor-respond with modern seismic hazard curves from recent publications by other authors for 12 Indonesian cities, including Jakarta, with some notable exceptions such as Ambon and Yogyakarta. In summary, our work on Gempa Nusantara demonstrates how a carefully vetted and well-documented historical record not only compliments studies of seismic hazard but is also itself an important standalone tool for the study of earthquake hazards in Indonesia.